Hierarchisches Optimierungskonzept für die Laststeuerung von Haushaltsgeräten - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (ETG-Fachtagung "Von Smart Grids zu Smart Markets")
Haushaltsgeräte aus der Klasse der "Weißen Ware" tragen mit etwa einem Drittel ($34,2%$ \citeBDEW2013) zum privaten Energieverbrauch bei. Diese Veröffentlichung präsentiert eine Struktur und die dafür notwendige optimale Betriebsstrategie für Weiße Ware in einer Umgebung mit Strompreisen, die wegen der Volatilität der Regenerativen Energien stark fluktuieren. Das vorgeschlagene Konzept nutzt dafür ein dezentrales Energiemanagementsystem, das über drei Hierarchieebenen verteilt ist: die Geräteebene, die Haushaltsebene und die Ortsnetzebene. Auf der Geräteebene nutzt dieses Konzept zusätzlich Betriebsflexibilitäten der Haushaltsgeräte aus.
Keywords: Energy management; hybrid energy storage system; self-optimization; multi-objective optimization; adaptive systems; pareto set; SFB614-D1; SFB614-D2; LEA-Publikation; Eigene

Request Driven Social Sensing - King, Thomas C.; Liu, Qingzhi; Polevoy, Gleb; de Weerdt, Mathijs; Dignum, Virginia; van Riemsdijk, M. Birna; Warnier, Martijn (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: crowd-sensing; crowdsourcing; data aggregation; game theory; norms; reciprocation; self interested agents; simulation

PEM fuel cell prognostics using particle filter with model parameter adaptation - Kimotho, James Kuria; Meyer, Tobias; Sextro, Walter (Prognostics and Health Management (PHM), 2014 IEEE Conference on)
Application of prognostics and health management (PHM) in the field of Proton Exchange Membrane (PEM) fuel cells is emerging as an important tool in increasing the reliability and availability of these systems. Though a lot of work is currently being conducted to develop PHM systems for fuel cells, various challenges have been encountered including the self-healing effect after characterization as well as accelerated degradation due to dynamic loading, all which make RUL predictions a difficult task. In this study, a prognostic approach based on adaptive particle filter algorithm is proposed. The novelty of the proposed method lies in the introduction of a self-healing factor after each characterization and the adaption of the degradation model parameters to fit to the changing degradation trend. An ensemble of five different state models based on weighted mean is then developed. The results show that the method is effective in estimating the remaining useful life of PEM fuel cells, with majority of the predictions falling within 5% error. The method was employed in the IEEE 2014 PHM Data Challenge and led to our team emerging the winner of the RUL category of the challenge.
Keywords: ageing; particle filtering (numerical methods); proton exchange membrane fuel cells; remaining life assessment; PEM fuel cell prognostics; PHM; RUL predictions; accelerated degradation; adaptive particle filter algorithm; dynamic loading; model parameter adaptation; prognostics and health management; proton exchange membrane fuel cells; remaining useful life estimation; self-healing effect; Adaptation models; Data models; Degradation; Estimation; Fuel cells; Mathematical model; Prognostics and health management

Closed-loop Control System for the Reliability of Intelligent Mechatronic Systems - Meyer , Tobias; Sextro, Walter (Proceedings of the Second European Conference of the Prognostics and Health Management Society 2014)
So-called reliability adaptive systems are able to adapt their system behavior based on the current reliability of the system. This allows them to react to changed operating conditions or faults within the system that change the degradation behavior. To implement such reliability adaptation, self-optimization can be used. A self-optimizing system pursues objectives, of which the priorities can be changed at runtime, in turn changing the system behavior. When including system reliability as an objective of the system, it becomes possible to change the system based on the current reliability as well. This capability can be used to control the reliability of the system throughout its operation period in order to achieve a pre-defined or user-selectable system lifetime. This way, optimal planning of maintenance intervals is possible while also using the system capabilities to their full extent. Our proposed control system makes it possible to react to changed degradation behavior by selecting objectives of the self-optimizing system and in turn changing the operating parameters in a closed loop. A two-stage controller is designed which is used to select the currently required priorities of the objectives in order to fulfill the desired usable lifetime. Investigations using a model of an automotive clutch system serve to demonstrate the feasibility of our controller. It is shown that the desired lifetime can be achieved reliably.
Keywords: self-optimization reliability adaptive

Method to Identify Dependability Objectives in Multiobjective Optimization Problem - Meyer , Tobias; Sondermann-Wölke, Christoph; Sextro, Walter (Conference Proceedings of the 2nd International Conference on System-Integrated Intelligence)
Intelligent mechatronic systems, such as self-optimizing systems, allow an adaptation of the system behavior at runtime based on the current situation. To do so, they generally select among several pre-defined working points. A common method to determine working points for a mechatronic system is to use model-based multiobjective optimization. It allows finding compromises among conflicting objectives, called objective functions, by adapting parameters. To evaluate the system behavior for different parameter sets, a model of the system behavior is included in the objective functions and is evaluated during each function call. Intelligent mechatronic systems also have the ability to adapt their behavior based on their current reliability, thus increasing their availability, or on changed safety requirements; all of which are summed up by the common term dependability. To allow this adaptation, dependability can be considered in multiobjective optimization by including dependability-related objective functions. However, whereas performance-related objective functions are easily found, formulation of dependability-related objective functions is highly system-specific and not intuitive, making it complex and error-prone. Since each mechatronic system is different, individual failure modes have to be taken into account, which need to be found using common methods such as Failure-Modes and Effects Analysis or Fault Tree Analysis. Using component degradation models, which again are specific to the system at hand, the main loading factors can be determined. By including these in the model of the system behavior, the relation between working point and dependability can be formulated as an objective function. In our work, this approach is presented in more detail. It is exemplified using an actively actuated single plate dry clutch system. Results show that this approach is suitable for formulating dependability-related objective functions and that these can be used to extend system lifetime by adapting system behavior.
Keywords: Self-optimization; multiobjective optimization; objective function; dependability; intelligent system; behavior adaptation

Towards self-adaptive caches: A run-time reconfigurable multi-core infrastructure - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2014 IEEE Intl. Conf. on Evolvable Systems (ICES))
Keywords: Linux; cache storage; embedded systems; granular computing; multiprocessing systems; reconfigurable architectures; Leon3 SPARe processor; custom logic events; evolvable-self-adaptable processor cache; fine granular profiling; integer unit events; measurement infrastructure; microarchitectural events; multicore embedded system; perf_event standard Linux performance measurement interface; processor properties; run-time reconfigurable memory-to-cache address mapping engine; run-time reconfigurable multicore infrastructure; split-level caching; Field programmable gate arrays; Frequency locked loops; Irrigation; Phasor measurement units; Registers; Weaving

Conceptualizing pronunciation as part of translingual/transcultural competence: New impulses for SLA research and the L2 classroom - Müller, Mareike (Foreign Language Annals)
This article aims to reconceptualize pronunciation teaching and learning according to the tenets of the 2007 MLA Report and its call for translingual/transcultural competence. The critical discussion of current teaching and research practices shows that the realm of pronunciation has benefitted little from debates on intercultural language learning. In order to link the teaching of pronunciation with learner needs in intercultural encounters, this article develops the concept of pronunciation‐as‐language. The theoretical exploration of this concept is supported by a narrative analysis of study-abroad learners’ accounts, contrasting learners’ perceptions of teaching practices with the complex role pronunciation plays in second language‐mediated interactions. The results underline the importance of pedagogical approaches that encourage the critical reflection on and creative use of pronunciation beyond structural elements and native‐speaker norms.
Keywords: critical language awareness; native‐speaker ideal; pronunciation; study abroad; translingual and transcultural competence

Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration